Expression of Pennisetum glaucum Eukaryotic Translational Initiation Factor 4A (PgeIF4A) Confers Improved Drought, Salinity, and Oxidative Stress Tolerance in Groundnut - Santosh Rama Bhadra Rao, Tata; Vijaya Naresh, Juturu; Sudhakar Reddy, Palakolanu; Reddy, Malireddy K.; Mallikarjuna, Garladinne (Frontiers in Plant Science, 2017)
Eukaryotic translational initiation factors belong to family of helicases, involved in multifunctional activities during stress and non-stress conditions. An eukaryotic translational initiation factor 4A (eIF4A) gene was isolated and cloned from semi-arid cereal crop of Pennisetum glaucum. In the present study, the PgeIF4A gene was expressed under the regulation of stress inducible Arabidopsis rd29A promoter in groundnut (cv JL-24) with bar as a selectable marker. The de-embryonated cotyledons were infected with Agrobacterium (LBA4404) carrying gene construct and generated high frequency of multiple shoots in phosphinothricin medium. Twenty- four T0 plants showed integration of both nos-bar and rd29A-PgeIF4A gene cassettes in genome with expected amplification products of 429 and 654 bps, respectively. Transgene copy number integration was observed in five T0 transgenic plants through Southern blotting analysis. Predicted Mendelian ratio of segregation (3:1) was noted in single gene integrated plants at T1 generation. The T2 homozygous lines (L1-5, L8-2 and L16-2,) expressing PgeIF4A gene were exhibited superior growth performance with respect to phenotypic parameters like shoot length, tap root length and lateral root formation under simulated drought and salinity stresses compared to the wild type. In addition, the chlorophyll retention was found to be higher in these plants compared to the control plants. Semi quantitative RT-PCR results confirmed the accumulation PgeIF4A transcript in L1-5, L8-3 and L16-2 plants imposed drought/salt stress. Further, the salt stress tolerance was associated with increase in oxidative stress markers, such as superoxide dismutase accumulation, reactive oxygen species scavenging and membrane stability in transgenic plants. Taken together our results confirmed that the PgeIF4A gene expressing transgenic groundnut plants exhibited better adaptation to stress conditions.